2019
DOI: 10.1093/pm/pny306
|View full text |Cite|
|
Sign up to set email alerts
|

Localization of Muscle Edema and Changes on Muscle Contractility After Dry Needling of Latent Trigger Points in the Gastrocnemius Muscle

Abstract: In this article, we aimed to describe what happens in skeletal muscle after dry needling intervention using magnetic resonance imaging (to show if there is edema) and tensiomyography (to measure contractile properties). At the same time, we describe the relationship between pain, edema, and contractility. Our results suggest that in asymptomatic patients, the application of dry needling over latent trigger points produce intra-muscular edema, an increase in muscle stiffness and an improved muscle contraction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 30 publications
1
28
0
1
Order By: Relevance
“…It is assumed that post-needling soreness is thought to be a consequence of the neuromuscular damage generated by the consecutive needling insertions into the muscle 45. This hypothesis has been supported by a recent study showing that muscle damage identified by magnetic resonance imaging after the application of dry needling over the gastrocnemius muscle was associated withpost-needling induced-pain 46. Other authors have associated the presence of post-needling to the number of local twitch responses elicited during the needling therapy 47…”
Section: Trigger Point Dry Needlingmentioning
confidence: 94%
“…It is assumed that post-needling soreness is thought to be a consequence of the neuromuscular damage generated by the consecutive needling insertions into the muscle 45. This hypothesis has been supported by a recent study showing that muscle damage identified by magnetic resonance imaging after the application of dry needling over the gastrocnemius muscle was associated withpost-needling induced-pain 46. Other authors have associated the presence of post-needling to the number of local twitch responses elicited during the needling therapy 47…”
Section: Trigger Point Dry Needlingmentioning
confidence: 94%
“…The automatic sympathetic neuron activation during the acupuncture intervention has also been correlated to the production of NO or vasoactive neuropeptides to modulate the vasodilation of the blood vessel to enhance the local blood volume (Jänig & Lisney, 1989; Kashiba & Uedo, 1991). In the other perspective, a consistent effort was on finding the anatomy acupoint sites in the meridian channel, by correlating to facial trigger points (Melzack et al ., 1977; Baraja-Vegas et al ., 2019), skin resistance (Ahn et al ., 2008), and interstitial flow (Zhang et al ., 2015). Among these attempted explanations, the neuron activation for both central nervous system and sympathetic nervous system is believed to be a clue to understand the acupuncture.…”
Section: Introductionmentioning
confidence: 99%
“…Within the strategies used for pain and myofascial dysfunction, Dry Needling is one of the common treatment methods, which works by intramuscular insertion of a fine monofilament needle into the trigger point until a first, short and sudden local contraction response is got , suggested as a spinal cord reflex linked to the sensitivity of dysfunctional motor and Research, Society and Development, v. 10, n. 5, e49510515198, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i5.15198 end plates allowing the mechanical effect of the needle to disable the stitch and promote pain relief (Al-Moraissi et al, 2020;Castro-Sánchez et al, 2020;Fernández-de-Las-Peñas & Nijs, 2019). These trigger points are painful nodules in the intramuscular region that involves hyperalgesic areas with referred pain, a stretched band and can be classified as active, when they cause sensory symptoms and spontaneous pain, and as latent when pain is only referred to when stimulated (Baraja-Vegas et al, 2019;Dalewski et al, 2019;Fernández-de-las-Peñas & Dommerholt, 2018).…”
Section: Introductionmentioning
confidence: 99%